Mapping of energy performance certificates (EPC) data applications - Pasichnyi, Oleksii (Royal Institute of Technology, 2018)
We performed systematic mapping of EPC data applications by time, geographical spread, data features & auxiliary data used, problem domains addressed and complexity of employed data analysis.
This mapping work was intended to answer the following questions:
Q1. Which research studies have used EPC data (hereafter “applications”)?
Q2. What input data were used by the EPC data applications?
Q3. Which problem domains were addressed by the EPC data applications?
Q4. How did the EPC data applications change within the study period?

Purpose:

To understand how the energy performance certificates (EPC) data has been used since introduction of the first national EPC registers.

Kartläggning av tillämpningar av EPC data. En mer detaljerad beskrivning är tillgängligt på den engelska katalogsidan: https://snd.gu.se/en/catalogue/study/SND1066
Kartläggning av tillämpningar av EPC data
Keywords: ENERGY; ENERGI; PERFORMANCE; PRESTANDA; Certification; Certifiering; Energy Engineering; Energiteknik